2012
DOI: 10.1007/s11605-012-1903-9
|View full text |Cite
|
Sign up to set email alerts
|

Nonabsorbable Suture Material in the Biliary Tract

Abstract: Nonabsorbable sutures may act as a nidus for stone formation within the biliary tree. A case of a large stone formed as a consequence of a Prolene suture within the biliary tract is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…a Tight coupling between magnets could be seen on POD 1; b On POD 40, the magnets had detached and moved toward the right iliac region; cOn POD 46, the magnets were expelled from the body. POD: post-operation day and is currently not recommended [18,19], especially for benign disease. Cai et al [20] reported a sutureless biliaryenteric anastomosis method where the biliary stump and jejunum were tied to an intraluminal stent to complete the biliary-enteric reconstruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…a Tight coupling between magnets could be seen on POD 1; b On POD 40, the magnets had detached and moved toward the right iliac region; cOn POD 46, the magnets were expelled from the body. POD: post-operation day and is currently not recommended [18,19], especially for benign disease. Cai et al [20] reported a sutureless biliaryenteric anastomosis method where the biliary stump and jejunum were tied to an intraluminal stent to complete the biliary-enteric reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…To simplify the CJ procedure, there are local and overseas reports on the use of gastrointestinal tubular anastomotic devices [3, 4, 17]. However, this results in non‐absorbable metal staples residue at the anastomosis and is currently not recommended [18, 19], especially for benign disease. Cai et al [20] reported a sutureless biliary‐enteric anastomosis method where the biliary stump and jejunum were tied to an intraluminal stent to complete the biliary‐enteric reconstruction.…”
Section: Discussionmentioning
confidence: 99%